The Lived Experiences of Filipino Incarcerated Mothers - Jervin Dinglasan Quicho; Angelica P. Alverde; Airah Montano; Krisha B. Najito; Maria Dianne A. Nisorrada (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This qualitative research paper will examine the experiences of incarcerated mothers in the Philippines, including their emotional hardships, how they manage such stressors, and their ways to live resilient lives. The study, based on semi-structured, in-depth questionnaires and a tool, thematic analysis, shows that maternal guilt, societal stigma, and institutional injustices enhance the impact of incarceration trauma, whereas faith, peer networks, and routines contribute to hope and self-development. The most significant results point to the two-fold concern of internalized shame and external constraints as the factors including limited family visitations, absence of post-release work, and shelter insecurity, which sustain marginalization cycles. The narratives of the participants highlight the potential of the transformative nature of the trauma-informed interventions and the prosocial conduct which redefines the guilt as agency and solidarity. Nonetheless, punitive policies and cultural stigma continue to pose a big hurdle in the reintegration process. The research proposes whole system changes, such as wider vocational training and family-based policies, in which maternal health takes precedence. This study can be applied to restorative justice systems capable of healing the soul and repairing the system by putting the voices of incarcerated others into the forefront, which in turn provides practical information to policy makers, correctional facilities, and community activists.